Price and Product Quality as Determinants of Tempeh Purchase Decisions in Local Food SMEs - Dewi Silvia; Birrul Walidain Sugiarto; Tomi Sani; Susi Indriyani (Apollo: Journal of Tourism and Business, 2026)
This study examines the effects of price and product quality on consumers’ purchase decisions of tempeh produced by local food small and medium-sized enterprises (SMEs) in Natar District, Indonesia. A quantitative associative approach was employed using a survey method. Data were collected from 325 respondents selected through purposive sampling, consisting of consumers who had purchased tempeh at least twice in the last month. A structured questionnaire with a five-point Likert scale was used, and the data were analyzed using multiple linear regression. The results indicate that price and product quality have positive and statistically significant effects on purchase decisions, both partially and simultaneously. Product quality demonstrated the strongest standardized effect among the examined predictors, indicating that consumers prioritize functional reliability and consumption-related risk reduction when purchasing staple-food products. These findings highlight the importance of maintaining consistent product quality and fair pricing strategies to enhance the competitiveness and sustainability of local food SMEs.